2012
DOI: 10.2135/cropsci2012.01.0059
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Field Paint Impacts Light Spectral Quality and Turfgrass Photosynthesis

Abstract: Athletic field paints are applied to turf surfaces with little or no acute injury. However, field managers notice chronic declines in turfgrass health after repeated applications. This study examines athletic field paint impacts on spectral quality and associated turfgrass photosynthesis. Growth chamber experiments evaluated effects of red and white athletic field paint as well as one, two, three, and four repeated weekly applications on total canopy photosynthesis (TCP) of perennial ryegrass {Lolium perenne L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…These include reductions in TCP, stomatal obstruction by paint pigments, and increased temperatures (McCarty et al, 2014;Reynolds et al, 2012Reynolds et al, , 2013. Black and blue paint resulted in the highest increase in VPD while also having the lowest transpirational water loss within the same VPD range as in the nonpainted study, where VPD was shown not to be a limiting factor on transpiration.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…These include reductions in TCP, stomatal obstruction by paint pigments, and increased temperatures (McCarty et al, 2014;Reynolds et al, 2012Reynolds et al, , 2013. Black and blue paint resulted in the highest increase in VPD while also having the lowest transpirational water loss within the same VPD range as in the nonpainted study, where VPD was shown not to be a limiting factor on transpiration.…”
Section: Discussionmentioning
confidence: 85%
“…Each of these could contribute to previously reported decreases in TCP and increases in canopy temperature in painted turfgrass canopies (Reynolds et al, 2012(Reynolds et al, , 2013. Given that paints are designed to entirely coat leaf surfaces, it is reasonable to suspect that gas exchange may be impeded by stomatal obstruction, potentially leading to carbon (C) starvation and reduced evaporative cooling.…”
Section: Athletic Field Paint Color Impacts Transpiration and Canopy mentioning
confidence: 99%
See 1 more Smart Citation
“…Darker paint pigments, such as black, blue, and purple, reduced NP, probably due to significantly reduced absorption of photosynthetically active radiation (PAR). Similarly, white also reduced NP, probably due to reflection of PAR (Reynolds et al, 2012). In both seasons, red had higher NP due to a smaller reduction in absorption in PAR compared with other colors.…”
Section: Net Photosynthesis and Canopy Temperatures For Overseeded Pementioning
confidence: 97%
“…A thletic‐field managers routinely paint playing surfaces for proper marking and aesthetics. Commonly, latex, water‐based paints specifically manufactured for turfgrass application are diluted at variable ratios with water before application (Reynolds et al, 2012). In the transition zone, bermudagrasses ( Cynodon spp.)…”
Section: Net Photosynthesis and Canopy Temperatures For Overseeded Pementioning
confidence: 99%